2019
DOI: 10.1186/s12863-019-0784-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genomic DNA variation in newly hybridized carp lineages derived from Cyprinus carpio (♀) × Megalobrama amblycephala (♂)

Abstract: BackgroundDistant hybridization can generate changes in phenotypes and genotypes that lead to the formation of new hybrid lineages with genetic variation. In this study, the establishment of two bisexual fertile carp lineages, including the improved diploid common carp (IDC) lineage and the improved diploid scattered mirror carp (IDMC) lineage, from the interspecific hybridization of common carp (Cyprinus carpio, 2n = 100) (♀) × blunt snout bream (Megalobrama amblycephala, 2n = 48) (♂), provided a good platfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Similarly, Luo et al 23 , demonstrated the positive relationship between growth and food consumption in flounder. In some species such as flatfish and cyprinids in general, size variation is a result of differential rates in feed consumption, aggressiveness and intraspecific competition under conditions of food scarcity.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, Luo et al 23 , demonstrated the positive relationship between growth and food consumption in flounder. In some species such as flatfish and cyprinids in general, size variation is a result of differential rates in feed consumption, aggressiveness and intraspecific competition under conditions of food scarcity.…”
Section: Discussionmentioning
confidence: 81%
“…These observations could to some degree reflect the increased difficulty of allopolyploidization in vertebrates relative to plants and suggest that common carp can serve as a model species for investigating vertebrate polyploidization. Other researchers established two bisexual fertile carp lineages from the hybridization of common carp (♀) and blunt snout bream (♂), providing insights into the role of hybridization in improving strains in aquaculture 62 . Alternatively, hybridization can decrease diversity and lead to genetic pollution in parental species or extinction of pure taxa in the wild if hybrids escape into natural waters 57,63,64 ; thus, hybrids require proper management.…”
Section: Germplasm Resources and Genetic Diversitymentioning
confidence: 99%
“…The mixed model was chosen for the Sox genes as no substitution model could be decided according the aa sequence. MrBayes was run for 10 million generations with two runs and four chains in parallel and a burn-in of 25%, and the analysis was terminated after the average standard deviation of the split frequencies fell under 0.01 (Luo et al, 2019). The final trees were visualized in FIGTREE (V1.4.4) software.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%